2023
DOI: 10.3390/v15071447
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Tembusu Virus in Mosquitoes in Northern Thailand

Abstract: Among emerging zoonotic pathogens, mosquito-borne viruses (MBVs) circulate between vertebrate animals and mosquitoes and represent a serious threat to humans via spillover from enzootic cycles to the human community. Active surveillance of MBVs in their vectors is therefore essential to better understand and prevent spillover and emergence, especially at the human–animal interface. In this study, we assessed the presence of MBVs using molecular and phylogenetic methods in mosquitoes collected along an ecologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
2
1
0
Order By: Relevance
“…The available evidence supports the notion that cluster 3 is the most primitive, indicating that cluster 1 and cluster 2 evolved from cluster 3 through mutation [20]. The TMUV strains belonging to cluster 3 have been detected in a diverse range of hosts, including mosquitoes [34,40], ducks [13], chickens [25,26], sparrows [27], and geese [35]. Notably, our research group has successfully isolated cluster 3 TMUV from geese as well.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The available evidence supports the notion that cluster 3 is the most primitive, indicating that cluster 1 and cluster 2 evolved from cluster 3 through mutation [20]. The TMUV strains belonging to cluster 3 have been detected in a diverse range of hosts, including mosquitoes [34,40], ducks [13], chickens [25,26], sparrows [27], and geese [35]. Notably, our research group has successfully isolated cluster 3 TMUV from geese as well.…”
Section: Discussionsupporting
confidence: 81%
“…Strains such as DK/TH/CU-56, isolated from Thailand in 2016, and SD14, isolated from China in 2014, are representative examples of this cluster [13]. P49_TH_2019, P73_TH_2019 and three other TMUV strains isolated in Thailand in 1992 and 2002 all belong to cluster 3 [34]. The available evidence supports the notion that cluster 3 is the most primitive, indicating that cluster 1 and cluster 2 evolved from cluster 3 through mutation [20].…”
Section: Discussionsupporting
confidence: 53%
“…Since 2010, most strains isolated in Thailand and a small number from China belong to Cluster 2.a, while most isolates from China are assigned to Cluster 2.b. In recent years, two different research groups have identified a new cluster called Cluster 3 within the TMUV group, which collects virus isolates from China and Thailand [15,[30][31][32][33] (Figure 2).…”
Section: Genomic Characteristicsmentioning
confidence: 99%